Assessment and interpretation of teachers' attitudes towards students with disabilities / Evaluación e interpretación de la actitud del profesorado hacia alumnos con discapacidad. Issue 3 (3rd July 2019) - Solís, Patricia; Pedrosa, Ignacio; Mateos-Fernández, Luz-María
Abstract: The process of including students with disabilities is necessarily influenced by teachers' attitudes towards them and towards their inclusion in education. After detecting the need to study the attitudes present in preschool and primary and secondary school teachers, this study was proposed as it was decided that an analysis of such attitudes could help to develop a better understanding of the current needs of the education system. This study analysed data on attitudes from a total of 175 teachers (29.10% male) working in state schools (50.30%) and semi-private schools in different autonomous communities of the Spanish state. An adapted version of the teacher questionnaire on attitudes towards students with special educational needs arising from disability was used. After analysing the psychometric properties of the questionnaire, further purification of these properties resulted in an assessment instrument comprising 22 items. It is worth highlighting the appraisal that teachers carry out of their training, the existence of resources, as well as their own level of involvement.